Development of a material-independent method for calculating the bending moment stresses acting on railway sleepers with constant cross-section. (August 2022) - Hoffmann, David; Freudenstein, Stephan
Railway sleepers experience bending moment stresses when subjected to railway traffic. These stresses are influenced by various parameters, such as loading, support conditions or the sleeper material. Approaches for the calculation of relevant bending moments currently exist only for prestressed concrete sleepers. For sleepers made of other materials, there are neither in-depth studies or literature on their bending stress nor calculation methods for determining the bending moments. Therefore, several 1000 calculations were carried out with the aim of depicting the stresses acting on sleepers in ballast. For these calculations, the theory of the beam on elastic foundation was used, with the help of which combinations of different support and loading conditions as well as of other parameters were investigated. By analysing the results focussing on the bending moments resp. the lever arms causative for these moments, it was possible to establish a correlation between the results obtained. Based on this correlation, a procedure for the determination of the lever arms independently from the load introduction length was developed. In combination with the scaling of the results over the elastic length of the sleepers, considering the track modulus as well as the sleeper geometry and material properties, this resulted in a generally valid, material-independent method for determining the moment stress of sleepers of constant cross-section, independent of the load introduction length.